2019
DOI: 10.1016/j.heliyon.2019.e01550
|View full text |Cite
|
Sign up to set email alerts
|

Credit constraints and soybean farmers' welfare in subsistence agriculture in Togo

Abstract: This study assesses the impact of credit constraints on soybean farmers' welfare in subsistence agriculture in Togo. In order to control potential sample selection bias, the endogenous switching regression method was adopted and data collected from a random sample of 500 soybean farmers were used. The results showed that farmers' age, being a member of the soybean organization and selling the soybean to a recognized NGO or to a private organization and growing cotton or cashew are the main determinants of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 60 publications
2
11
0
1
Order By: Relevance
“…The negative coefficient of extension access in this study implies that smallholder cassava farmers with access to agricultural extension services are less technically inefficient collated with farmers without access to extension services. This finding is in line with that of Ali and Awade (2019), who found that access to extension services significantly improves the productivity of credit-constrained soybean farmers in Togo. Enhancements in the scope and delivery of agricultural extension services would translate into significant improvements in the TE of farmers in the district.…”
Section: Technical Efficiency Of Cassava Farmerssupporting
confidence: 91%
“…The negative coefficient of extension access in this study implies that smallholder cassava farmers with access to agricultural extension services are less technically inefficient collated with farmers without access to extension services. This finding is in line with that of Ali and Awade (2019), who found that access to extension services significantly improves the productivity of credit-constrained soybean farmers in Togo. Enhancements in the scope and delivery of agricultural extension services would translate into significant improvements in the TE of farmers in the district.…”
Section: Technical Efficiency Of Cassava Farmerssupporting
confidence: 91%
“…The scarcity of agricultural economic goods and insufficient access to credit might affect farmer's well-being, which consists of farm production, sustenance, and food security ( Ali and Awade, 2019 ; Awotide et al., 2015 ; Asiedu et al., 2013 ). Farmers could procure farm implements, but they are urged by credit constraints to confine their spending and production preferences ( Dong et al., 2012 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…(2016) ; Muayila and Tollens (2012) , and Baiyegunhi et al. (2010) A recent study by Ali and Awade (2019) utilized production and net revenue as an indicator to measure farmer's welfare.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A theory is also based on the link between access to credit and its influence on farmers' income and welfare. Ali and Awade (2019) establish that access to credit for soybean farmers in Togo has a positive effect on their income and welfare.…”
Section: Introductionmentioning
confidence: 99%